MODEL SEIDR DALAM STUDI PENYEBARAN TUBERKULOSIS: ANALISIS INTERVENSI DIAGNOSIS DAN DAMPAKNYA TERHADAP DINAMIKA INFEKSI - Sila Rizqina; Muhammad Afief Balya; Yuni Yulida; Muhammad Ahsar Karim; Hermei Lissa (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2025)
Pulmonary Tuberculosis (TB) is a contagious infectious disease caused by Mycobacterium tuberculosis. A person with tuberculosis serves as a source of transmission to the surrounding population. One way to minimize the transmission is through the implementation of effective diagnostic intervention. One approach to understanding the dynamics of TB spread is through the SEIDR epidemiological mathematical model, which includes susceptible, exposed, infectious, diagnosed, and recovered individuals. This study begins by explaining the construction of the SEIDR model, followed by determining the disease-free equilibrium point, the basic reproduction number, local stability analysis of the disease-free equilibrium, and sensitivity analysis. The final step involves conducting numerical simulations and interpreting the results obtained. There are two equilibrium points derived from the model: the disease-free equilibrium and the endemic equilibrium. The disease-free equilibrium point is asymptotically stable if the basic reproduction number is less than one, while the endemic equilibrium point is determined through simulation. Based on the simulation, it is found that the system experiences an outbreak when the basic reproduction number is greater than one. Sensitivity analysis shows that the birth rate has the highest positive influence on the basic reproduction number, while the natural death rate has the highest negative influence on the basic reproduction number. Numerical simulation results show that when transmission is high, the number of diagnosed individuals increases sharply, while the susceptible and exposed populations decrease drastically; conversely, if transmission is suppressed, active cases decline until they are completely eliminated. Therefore, effective interventions are crucial to reduce transmission and to strengthen diagnostic systems in order to achieve TB elimination at the population level